Analysis of steady state and non-steady state corneal permeation of diclofenac. Issue 38 (29th March 2016) - Mohapatra, Rajaram; Mallick, Subrata; Nanda, Ashirbad; Sahoo, Rudra N.; Pramanik, Arunima; Bose, Anindya; Das, Debajyoti; Pattnaik, Lolly
Abstract : The present study was undertaken for characterization of the steady state and non steady state corneal permeation kinetics of diclofenac potassium (DCP) using statistical moment theory. Abstract : The present study was undertaken for characterization of the steady state and non steady state corneal permeation kinetics of diclofenac potassium (DCP) using statistical moment theory. Hydrogel films containing DCP in a hydroxypropyl methylcellulose (HPMC) matrix were prepared by a casting method, and the steady state and non-steady state corneal permeation parameters of diclofenac were evaluated using statistical moment analysis. The correlation coefficient ( r ), coefficient of non-determination and standard error of estimate (SEE) results indicated a good Level "A" correlation between in vitro dissolution and ex vivo steady state permeation of DCP from all the hydrogel formulations. SEM, XRD and DSC studies suggested the inhibition of the crystal growth and partial amorphization of diclofenac in the film. One way analysis of variance (ANOVA) followed by Dunnett's test revealed that all the hydrogel films containing plasticizer (L2, L3 and L4) show very high significant difference of extent of permeation in non-steady state (EPN), extent of permeation in lag time (EPL), extent of permeation in steady state (EPS) and total amount permeated in 360 min (TAP) from the control film containing no plasticizer (L1) related to highly improved permeation. Marked anti-inflammatory activity has been observed after application of the hydrogel film. The binding configuration of DCP-HPMC using docking calculations indicated drug–excipient interaction at the molecular level. Steady state and non-steady state corneal permeation parameters have been evaluated successfully using statistical moment analysis, and highly improved permeation has been observed when compared to the parameters of the film with the control.